UDC 661.152.5 STUDY OF INTERACTION OF COMPONENTS IN ZnSO4 – NH4H2PO4 – H2O SYSTEM - Maxkamova, Dilnoza; Turayev, Zokirjon; Dedaboyeva, Mahliyo (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
To theoretically substantiate the interaction of zinc sulfate with monoammonium phosphate, an isomolar series was used, based on the ratio of the components ZnSO4 and NH4H2PO4.